Teoretski temelji ocenjevanja osebnosti v klinični psihologiji - Benedik, Emil (Psihološka obzorja (Ljubljana), 2010)
The paper emphasizes an important role of personality assessment in clinical psychology, leading theoretical and methodological perspectives, as well as the need for integrating different concepts and methods in personality assessment. Personality assessment in clinical psychology represents methodological frame for better understanding and treatment of psychological (mental) disorders. Two principles for personality assessment prevail: one is based on psychological concepts of personality and statistical methodology, and the other relies on findings from clinical practice (clinical psychology, psychiatry and related fields). Since we do not yet have a generally accepted paradigm of personality assessment, clinical psychology needs unified concepts and methodology for personality assessment. Several authors have attempted to integrate and unify psychological concepts and methodology of assessment in the last decade. This is the path to development of clinical psychology and psychological science in general.
Keywords: klinična psihologija; osebnost; personality; testiranje; ocenjevanje